2018
DOI: 10.1017/s0140525x18001395
|View full text |Cite
|
Sign up to set email alerts
|

Serial effects are optimal

Abstract: In the target article, Rahnev & Denison (R&D) use serial effects as an example of suboptimality.We show here that serial effects can be beneficial to perception, serving to reduce both error and response times in a near-optimal fashion. Furthermore, serial effects for stable attributes are positive, whereas those for changeable attributes are negative, demonstrating that they are engaged flexibly to optimize performance.We read with great interest the article by Rahnev & Denison (R&D), reporting both a wide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…We next examined how response precision (σ) varied as a function of Δθ and found that responses were more precise around small trial-to-trial orientation changes (Figure 1F), again consistent with previous reports (Cicchini and Burr, 2018). We quantified this difference in precision by splitting trials into ‘close’ and ‘far’ bins (greater than or less than 30° separation) and confirmed that responses following ‘close’ stimuli were more precise ( t (46)=-3.72, p =0.0003, paired 1-tailed t-test, Figure 1G, see Response Precision).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We next examined how response precision (σ) varied as a function of Δθ and found that responses were more precise around small trial-to-trial orientation changes (Figure 1F), again consistent with previous reports (Cicchini and Burr, 2018). We quantified this difference in precision by splitting trials into ‘close’ and ‘far’ bins (greater than or less than 30° separation) and confirmed that responses following ‘close’ stimuli were more precise ( t (46)=-3.72, p =0.0003, paired 1-tailed t-test, Figure 1G, see Response Precision).…”
Section: Resultssupporting
confidence: 87%
“…and the trial sequence was ordered so that a near oblique orientation was always followed by a near cardinal orientation (n=7). This was implemented to maximize our ability to observe serial dependencies in our binary response data as it is typically strongest around orientation changes of 20° and is more pronounced around oblique orientations (Cicchini and Burr, 2018). The remaining participants completed both blocks with uniform and blocks with binned stimuli (n=14).…”
Section: Methodsmentioning
confidence: 99%
“…The fact that these context effects were stronger in participants with no musical training is consistent with the hypothesis that influence of prior context increases as the uncertainty of the current representation increases ( Cicchini et al. 2018 ; Cicchini and Burr 2018 ). Nonmusicians, whose meter perception was overall less robust to input degradation, would rely more on the recent context to make better sense of the degraded input (see Cicchini et al.…”
Section: Discussionsupporting
confidence: 84%
“…However, although a logarithmic transformation is a static nonlinearity, the Bayesian account suggests that the effects should be dynamic because the prior may be recalculated on every trial. Previous work has shown that the effects are indeed dynamic (Cicchini et al, 2014), following the pattern of results of serial dependence (attraction to the previous stimulus) observed for many perceptual phenomena, such as orientation and face perception (Cicchini & Burr, 2018; Liberman et al, 2014; Taubert et al, 2016). Serial effects were strongest for higher numbers and predicted a compressive behavior in the number-line task, without evoking the idea of intrinsic logarithmic coding.…”
supporting
confidence: 54%